La colaboración de la ciudadanía con la Policía Nacional en la parroquia Panguintza, cantón Centinela del Cóndor, provincia Zamora Chinchipe, en materia de seguridad pública, periodo 2020-2022. - Avila Rosales, Verónica Maribit (2023)
The purpose of this research was to analyze the collaboration of citizens with the National Police in Panguitza parish, located in Centinela del Condor canton, Zamora Chinchipe province in terms of public safety period 2020-2022, through the recognition of the strategies implemented by the National Police to promote the active participation of citizens in matters of security and the effectiveness of these strategies, in addition to the elaboration of the research proposal defined through an action plan in order to promote the collaboration of citizens with the National Police in the parish of Panguintza. In order to carry out this study, a methodology with a mixed approach, analytical-synthetic and deductive methods of analysis was established. In addition, the calculation of the sample determined through the sample distribution by neighborhood in Panguitza parish was carried out, likewise, the information collection instruments used were the interview and the survey, the latter being applied through the KoboCollect application on a Smartphone. The results obtained allowed determining the lack of collaboration and participation of citizens with the National Police, which limits the management of collective welfare actions and decision making by the law enforcement authority. With this result, it was possible to establish a research proposal structured by social management activities that encourage the collaboration of citizens within the parish, promoting greater participation and cooperation on issues related to public safety.